Exploring the relationship of social media usage and multitasking of social media on self-efficacy and academic performance - Mahir Tahrir Salih Mohammed,; Faridah Ibrahim,; Norzita Yunus, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Social media usage is known to harness new lifestyle among the youth. Use of social media promotes the negative as well as positive consequences for the students in general and academic life. This study examined the relationship between social media usage, multitasking of social media, and students' academic self-efficacy on students' academic performance among Malaysian youth. The current work also evaluates the mediating effect of students' academic self-efficacy on social media usage and social media multitasking on their academic performance. This study embraced a cross-sectional research design and quantitative data collected from 644 Malaysian students of higher education institutions. The collected data were analysed using SPSS v23 and PLS-SEM-based SmartPLS 3.1. The findings revealed that social media usage and social media multitasking are positively and significantly related to students' self-efficacy. Moreover, the results also showed that social media usage and multitasking, and students' self-efficacy are significantly associated with their academic performance. The results also exposed the mediational effect of students' self-efficacy on the relationship between social media multitasking and students' academic performance in higher education. The study recommends that by initiating the self-efficacy program in promoting social media's academic use and multitasking among Malaysian higher education students would result in better performance.